Complexing of Reduced Technetium and Tin(II) by Chelating Phosphate Compounds - Schümichen, C.; Hohloch, M.; Hoffmann, G. (Nuklearmedizin - NuclearMedicine, 1979)
The in vitro stability of 99mTc- and 113Sn-pyrophosphate and -ethane-1, hydroxy-1, diphosphonate (EHDP) complexes was studied by varying the mode of preparation. The 1-hr distribution in the rat was used as an indicator for complex formation or destruction. A maximum of bone uptake and urinary excretion and a minimum of soft tissue concentration was obtained if there was an excess of phosphate in relation to tin(II) in the equilibrium. Formation of tin(II) colloid was favoured in the presence of an excess of tin(II) in the equilibrium, 99mTc colloid occurred with some delay. After dilution in neutral normal saline the chelates were more or less destroyed, as shown by a 113Sn(II) colloid formation whereas the 99mTc-phosphate complexes were transformed into a 99mTc kidney agent. At pH 11 the 113Sn(II)-phosphate complexes proved to be stable, the 99mTc-phosphate complexes were also transformed into the 99mTc kidney agent. Oxidation of all tin(II) in the equilibrium by hydrogen peroxide did not change the distribution patterns of 113Sn, 99mTc was oxidized to pertechnetate. In general complexes between tin(II) and chelating phosphate compounds proved to be more stable than those with reduced technetium. EHDP was found to form stronger complexes with tin(II) and reduced technetium than pyrophosphate.